Crosstalk between anticancer drugs and mitochondrial functions - Kuleshwar Sahu; Urvashi Langeh; Charan Singh; Arti Singh, PHD (Elsevier, 2021)
Chemotherapy is an important component of cancer treatment, which has side effects like vomiting, peripheral neuropathy, and numerous organ toxicity but the most significant outcomes of chemotherapy are cognitive impairment, which is mainly referred to as chemobrain or CICI (chemotherapy-induced cognitive impairment). It is characterized by difficulty with language, concentrating, processing speed, learning, and memory, as it affects the hippocampus areas of the brain. Mitochondrial dysfunction and oxidative stress are one of the major mechanisms causing chemobrain. The generation of reactive oxygen species (byproducts of oxidative phosphorylation) mainly occurs in mitochondria that play a prominent role in the induction of oxidative stress. The homeostasis of ROS in the mitochondria is maintained by mitochondrial antioxidant mechanism via enzymes like catalase, glutathione, and superoxide dismutase. Lungs and breast cancer are the two most common types of cancer, which are the most leading cancers in the world with about 4.18 million cases. In this review we exposed the current knowledge regarding chemotherapy-induced oxidative stress and mitochondrial dysfunction to cause cognitive impairment.We especially focused on the antineoplastic agent (ADRIAMYCIN, CYCLOPHOSPHAMIDE), platinum group agent CISPLATIN, antimetabolite agents (METHOTREXATE), and nitrogen mustard agent (CARMUSTINE) which increase oxidative stress and inflammatory markers in the PNS (peripheral nervous system) as well as the central nervous system. We also highlight the behavioural and functional changes in the brain.